Multi-agent system finite-time consensus control in the presence of disturbance and input saturation by using of adaptive terminal sliding mode method. Issue 1 (1st January 2019) - Mirabdollahi, S. E.; Haeri, M.
Abstract: The paper develops finite-time consensus control for multi-agent systems by considering disturbances and input saturation. A new adaptive-terminal sliding mode control is suggested to solve consensus control within a finite time. Two cases are solved in the paper. In the first case, it is assumed that disturbances are with known upper. To achieve the consensus purpose within the finite time, in this case, the control inputs are designed based on terminal sliding mode technique by considering the input signal saturation. Also, the control inputs are modified to reduce the high dependency of reaching times to initial speeds. In the second case, the agents are subjected to disturbances with unknown upper bounds. To handle the problem, the control signals are acquired by combining the adaptive and terminal sliding mode methods. By considering saturation boundary and disturbances with unknown upper band, a new adaptive-terminal sliding mode method is designed to control the multi-agent system in reduced settling and reaching times. The proposed techniques efficiency is confirmed by numerical simulations.